Ferric carboxymaltose in patients with restless legs syndrome and nonanemic iron deficiency: A randomized trial. Issue 10 (23rd June 2017) - Trenkwalder, Claudia; Winkelmann, Juliane; Oertel, Wolfgang; Virgin, Garth; Roubert, Bernard; Mezzacasa, Anna
Abstract: Background : Compromised iron status is important in restless legs syndrome pathophysiology. We compared the efficacy and tolerability of ferric carboxymaltose (single intravenous dose) versus placebo for restless legs syndrome treatment in iron‐deficient nonanemic patients. Methods : Patients with moderate to severe restless legs syndrome and serum ferritin < 75 μg/L (or serum ferritin 75‐300 μg/L and transferrin saturation < 20%) were randomized to ferric carboxymaltose (1000 mg iron) or placebo. Mean change difference between ferric carboxymaltose and placebo in International Restless Legs Syndrome Severity Scale score from baseline to week 4 was the primary end point; week 12 was a secondary end point. Results : Ferric carboxymaltose treatment (n = 59) led to nonsignificant improvement over placebo (n = 51) in International Restless Legs Syndrome Severity Scale score at week 4 (difference [95% confidence interval], ‐2.5 [‐5.93 to 1.02], P = 0.163), reaching significance by week 12 (‐4.66 [‐8.59 to ‐0.73], P = 0.021). Conclusions : In patients who responded to treatment, ferric carboxymaltose may require more time to stabilize restless legs syndrome than previously assumed. © 2017 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.